Coherent J/ψ photoproduction at midrapidity in Pb - Pb collisions at √sNN=5.02 TeV - Acharya, S.; Agarwal, A.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Akishina, V.; et al. (ELSEVIER, 2025)
The coherent J/psi photoproduction cross section is measured for the first time at midrapidity in peripheral to semicentral Pb - Pb collisions at root s(NN) = 5.02 TeV. The centrality differential cross section d sigma/dy is reported for the centrality range 40-90%, together with the doubly-differential cross section d(2)sigma/dydp(T), extracted in two peripheral centrality classes. The J/psi mesons are reconstructed in the dielectron channel, in the rapidity interval |y| < 0.9 using the ALICE central barrel detectors. The J/psi cross section at midrapidity is statistically compatible to the earlier ALICE measurement at forward rapidity and at the same centre-of-mass energy, and shows only a mild centrality dependence over the covered range. Several sets of theoretical calculations taking into account the hadronic overlap in the collisions but ignoring possible final-state effects from a hot expanding medium are found to give a fairly good description of the current measurements within uncertainties.
Keywords: Charmonium; Ultra peripheral heavy-ion collisions; Coherent photoproduction; MONTE-CARLO; PHYSICS; Astronomy & Astrophysics